IMPLEMENTASI MANAJEMEN PEMASARAN JASA PENDIDIKAN DALAM MENINGKATKAN KEPUASAN PELANGGAN DI MADRASAH ALIYAH TERPADU (MAT) DARUL FALLAH BOGOR - Sarifudin Sarifudin; Rahendra Maya (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2019)
The management of marketing education services will be good if done correctly and professionally. The aim of the marketing management of education services is to facilitate the institution in marketing its educational services to the community. The purpose of this study is to be able to find out how the implementation of the mix strategy in the marketing management of education services in the Darul Fallah Integrated Aliyah Madrasah (MAT) Bogor. This scientific research uses qualitative methods by collecting data from field observation activities, interviews with relevant sources, and taking documentation from the research site. The marketing mix of education services in MAT Darul Fallah Bogor includes: (1) Product strategy; (2) Price Strategy; (3) Place Strategy (location); (4) Promotion Strategy; (5) People Strategy; (6) Physical Evendece Strategy; and (7) Process Strategy. In addition, this study also discusses the development of marketing education services in MAT Darul Fallah Bogor from year to year and various kinds of educational services products offered so that consumers are more interested in seeing firsthand the advantages of this school.Keywords: management, marketing, education services, satisfaction.